Druid theatre's economics: the first decade - Shelley Troupe (Ilha do Desterro)
This article considers the relationship between Druid Theatre's productions and its administration during the company's first decade by investigating the links between three features:  the company's fundraising practices; Druid's infrastructure development in terms of personnel and physical space; and the organisation's programming choices.  Druid's artistic partnership with Irish playwright Tom Murphy is also examined as it assisted in launching Druid's international touring when Murphy's Conversations on a Homecoming was the first Druid production to travel outside of the United States/United Kingdom festival circuit.